New MLFQ Scheduling Algorithm for Operating Systems Using Dynamic quantum - Kadry, Seifedine; Bagdasaryan, Armen (Statistics, Optimization & Information Computing, 2015)
The new design of multilevel feedback queue will depend on usage new technique in computing the quantum to produce (ADQ) Auto Detect Quantum which is relied on the burst of each process has enrolled to the system. By summating the burst time of each process has arrived and dividing it by the number of available processes, we can obtained the dynamic quantum in each level of scheduling. The processes are scheduled and shifted down from queue to other according to their remaining bursts time that should be updated periodically. Every queue has a unique auto detected quantum which is gradually increased or decreased from top level to bottom level queues according to the case of arriving processes. Depending on the results of graphical simulating algorithm on cases study, we can discover that a dynamic quantum is very suitable to accommodate low priority processes that still for a long duration to complete their requests, i.e. avoid the starvation of CPU- bounded processes. Although, it stills compatible with high priority processes (I/O-Bounded) to provide a fair interactivity with them. In comparison to traditional MLFQ the performance of the new scheduling technique is better and practical according to the applied results. Additional, we developed suitable software to simulate the new design and test it on different cases to prove it.